Ethical Issues in Suicide Research - Mozaffor, M; Nurunnabi, ASM; Shahriah, S (Journal of Psychiatrists' Association of Nepal, 2020)
Introduction: Quality research is needed in order to better understand, appropriately respond to, and reduce the incidence of suicide, which must be ethically sound as well. However, in South Asian region, there is a lack of knowledge and clarity around the nature of ethical problems related to suicide research and how to resolve them. This review work aims to describe the possible ethical problems and how to ensure ethical practice in different types of suicide research, especially involving groups of people who are or who have been suicidal.Material And Method: This review was prepared through an extensive searching of published articles in 3 databases - Google, HINARI and PubMed. However, some institutional guidelines were also taken into considerations. Key words used for searching were ‘suicide’, ‘suicidal’, ‘ethics’, ‘ethical issues’ and ‘ethical research’. A total of 18 journal articles and 3 guidelines were finally selected for this review.Results: Major concerns or ethical issues are accessing the population, potential harm to participants or the researcher, researchers’ competency, securing trust and confidence, maintaining confidentiality, providing support to the participants, and responding sensitively to the needs of the family involved.Conclusion: Ethical research on suicide, especially involving people with suicidal ideation requires both procedures to protect the study participants, and consideration of ethical dilemmas (before, during and after research) as an ongoing negotiated process. The findings of this research provide a collection and compilation of views held by number of researchers, bioethicists, ethics committee members as well as institutions.